2007
DOI: 10.4081/ijas.2007.1s.701
|View full text |Cite
|
Sign up to set email alerts
|

Pig, F1 (wild boar x pig) and wild boar meat quality

Abstract: Sixteen carcasses of wild boars, pigs, hybrids F1 (wild boar x pig) and reared wild boar have been examined to study the meat quality and the fatty acid composition. Four carcasses came from hunted wild boars and twelve from animals reared in outdoor pens till nine months of age. The meat produced by the hunted wild animals, although not marketable, offers the best quality and nutritional characteristics. The use of hybrids reared in outdoor pens can approximate or equalize the hunted wild boars meat traits. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 1 publication
4
13
3
Order By: Relevance
“…There was a slight increase in the pH value recorded between the 48 and 360 h post-mortem, but the final pH value did exceed the normal range of pH given in the literature for hunted wild boar meat. Compared to this study, a lower value of pH measured 24-h post-mortem was presented in other research papers (Marchiori and Fel ıcio 2003;Marsico et al 2007;Cifuni et al 2014) for the longissimus muscle of wild boars (5.62-5.64, 5.46 and 5.48, respectively). In their study, Florek et al (2017) report even higher pH for wild boar meat kept frozen in vacuum pouches for 60 days.…”
Section: Value Of Ph and Colour Coordinatescontrasting
confidence: 80%
“…There was a slight increase in the pH value recorded between the 48 and 360 h post-mortem, but the final pH value did exceed the normal range of pH given in the literature for hunted wild boar meat. Compared to this study, a lower value of pH measured 24-h post-mortem was presented in other research papers (Marchiori and Fel ıcio 2003;Marsico et al 2007;Cifuni et al 2014) for the longissimus muscle of wild boars (5.62-5.64, 5.46 and 5.48, respectively). In their study, Florek et al (2017) report even higher pH for wild boar meat kept frozen in vacuum pouches for 60 days.…”
Section: Value Of Ph and Colour Coordinatescontrasting
confidence: 80%
“…The terminal sire can have a strong influence on the fat quality and fatty acid composition (Alonso et al, 2009;Suzuki et al, 2003;Zhang et al, 2007). However, in this study, there were no significant differences of SFA, MUFA and PUFA in LD between the Yorkshire-sired and Landrace-sired hybrids (Table 3), and this is in agreement with the results of other authors who have found no breed and crossbred genotype (Marsico et al, 2007;Suzuki et al, 2003) difference in concentration of SFA of intramuscular fat in LD. This is in contrast with the findings of Ramı´rez and Cava (2007), who found a lipid fraction differences in different Iberian  Duroc genotypes and Zhang et al (2007), who reported the breed (Duroc, Hampshire, Landrace and Yorkshire) as terminal sires, influence on SFA and other fatty acid composition of the LD muscle.…”
Section: Fatty Acid Composition Of Muscle Lipidssupporting
confidence: 93%
“…Although the anatomy between both is, in principle, comparable, there are important differences that may affect the decomposition process. Wild boar have thicker skin than domestic pigs, densely covered with bristles [43,44]. It is therefore not surprising that the skin remains intact for a longer time, thus retaining carcass moisture, protecting the interior from vertebrate scavengers, and possibly slowing down the activity rate of maggots.…”
Section: Discussionmentioning
confidence: 99%